Facilitating and Inhibiting Factors of Sexual Behavior among Migrants in Transition from Mexico to the United States - Guerra-Ordoñez, Jesús Alejandro; Benavides-Torres, Raquel A.; Zapata-Garibay, Rogelio; Onofre-Rodríguez, Dora Julia; Márquez-Vega, María Aracely; Zamora-Carmona, Gabriela (Frontiers in Public Health, 2017)
Introduction Human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) is one of the most prevalent infectious diseases in the border region of Mexico due to the flow of migrants under desperate conditions, encouraging casual and unprotected sex. Since this has become a binational public health problem, it is important to understand the factors that predict these sexual behaviors. The aim of the current study was to investigate the facilitators and inhibitors of transition in the sexual behavior of migrants from two border regions on the Mexico–United States (US) border. Methods This was a predictive and cross-sectional study. A sample of 256 migrants in shelters for migrants on the border between Mexico and US were selected through systematic random sampling. Predictor variables investigated for effect on the safe sexual behavior (SSB) of the migrant were reasons for having sex; sexual attitudes; sexual machismo; knowledge about HIV; access to health services; and social discrimination. Results The sample was predominantly male (89.5%), with 46.1% reporting being single. The average age was 33.38 years (SD = 9.73) and the average number of years of education reported was 8.05 (SD = 3.37). A permissive sexual attitude and sexual machismo both correlated with condom use (rs = 0.130, p < 0.01 and rs = −0.174, p < 0.01, respectively). Regression analysis showed that a permissive sexual attitude decreased the practice of safe sex (β = 0.17, t = 4.16, p < 0.001), as did sexual machismo (β = −0.28, t = −4.83, p < 0.001) and HIV knowledge (β = −0.11, t = −2.62, p = 0.006). Discussion It was found that access to health services did not influence the SSB of migrants, as suggested by the literature. However, a permissive sexual attitude, sexual machismo, and HIV knowledge were all variables capable of predicting SSB. It is recommended that the study is extended to study migrant populations from other parts of the border, as well undertaking as a qualitative approach to explore new variables.